2017
DOI: 10.3201/eid2312.171086
|View full text |Cite
|
Sign up to set email alerts
|

Deaths among Wild Birds during Highly Pathogenic Avian Influenza A(H5N8) Virus Outbreak, the Netherlands

Abstract: During autumn–winter 2016–2017, highly pathogenic avian influenza A(H5N8) viruses caused mass die-offs among wild birds in the Netherlands. Among the ≈13,600 birds reported dead, most were tufted ducks (Aythya fuligula) and Eurasian wigeons (Anas penelope). Recurrence of avian influenza outbreaks might alter wild bird population dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
137
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(144 citation statements)
references
References 11 publications
(14 reference statements)
6
137
0
1
Order By: Relevance
“…We plotted the geographic locations where the HPAI H5N8 virus was detected (Figure 1, panel A). Tufted ducks were the most affected bird species in November and Eurasian wigeons ( Anas penelope ) in December ( 21 ). However, many species of wild birds became infected, including diving and dabbling ducks as well as mute swans, grebes, gulls, and buzzards ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We plotted the geographic locations where the HPAI H5N8 virus was detected (Figure 1, panel A). Tufted ducks were the most affected bird species in November and Eurasian wigeons ( Anas penelope ) in December ( 21 ). However, many species of wild birds became infected, including diving and dabbling ducks as well as mute swans, grebes, gulls, and buzzards ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Tufted ducks were the most affected bird species in November and Eurasian wigeons ( Anas penelope ) in December ( 21 ). However, many species of wild birds became infected, including diving and dabbling ducks as well as mute swans, grebes, gulls, and buzzards ( 21 ). An HPAI virus of subtype H5N5 was detected in 2 birds, a tufted duck found dead near Monnickendam, and a mute swan near Groningen.…”
Section: Resultsmentioning
confidence: 99%
“…H5N6 viruses may have been less prevalent than H5N8 viruses in the wild bird population, or the exposure to H5N8 viruses in the previous year may have resulted in immunological protection against infection with H5N6 virus. Furthermore, early in the H5N8 2016 epidemic, the virus was mainly detected in migratory water birds (tufted ducks and Eurasian wigeons), whereas later in the epidemic also birds of prey were infected (Kleyheeg et al., ). These predators were most likely infected by feeding on infected preys.…”
Section: Discussionmentioning
confidence: 99%
“…Kleyheeg et al (2017) also described clinical signs in wild birds thought to be infected with HPAIV A(H5N8). Assuming that no migration occurred, it was estimated that up to 25% of the local population of tufted ducks might have died, which might affect population dynamics substantially.…”
Section: Pathogenicity In the Affected Speciesmentioning
confidence: 99%
“…Kleyheeg et al (2017) reported on wild bird mortality during a HPAIV A(H5N8) outbreak in the Netherlands, starting in November 2016. Kleyheeg et al (2017) reported on wild bird mortality during a HPAIV A(H5N8) outbreak in the Netherlands, starting in November 2016.…”
Section: Pathogenicity In the Affected Speciesmentioning
confidence: 99%